Salpingectomy for the Prevention of Epithelial Ovarian Cancer (Obstetrics & Gynecology, 2026)
This Clinical Practice Update provides updated information further supporting the benefit of complete, bilateral salpingectomy at the time of obstetric and gynecologic surgery and to expand the availability of salpingectomy during nongynecologic abdominopelvic surgery for the primary prevention of epithelial ovarian cancer. This document updates Committee Opinion No. 774, Opportunistic Salpingectomy as a Strategy for Epithelial Ovarian Cancer Prevention (Obstet Gynecol 2019;133:e279–84).